KINETIN AND NAA IN VITRO MULTIPLICATION OF PAPAYA TREE ‘TAINUNG 01’ - SCHMILDT, Omar; SCHMILDT, Edilson Romais; AMARAL, José Augusto Teixeira do (Scientia Agraria, 2007)
The commercial planting of the papaya tree, done traditionally through seeds, it presents limitations due to the free pollination, resulting in variations in her descent for the decay of the genotypes, committing the quality of the farmings. The micropropagation appears as viable alternative for the production of exempt seedlings of diseases and with the desirable genetic characteristics of the main plant. The objective of this work was it of identifying the best combination of different levels Kinetin (5.38; 10.76 and 21.52 mg L-1) and NAA (0.093; 0.931 and 1.862 mg L-1) for the establishment in vitro in MS culture medium. The used explants were apical sections of juvenile plants of papaya tree ‘Tainung 01’ with 10 weeks of aged. After 30 days the rates of surviving cultures were evaluated, reactivate cultures, the calluses of mass and, to each subculture the multiplication rate of the explants. The explants that best formed rosette of leaves they were inoculated in proliferation medium during five subcultures, with transplantation every 30 days. The best results for the survival percentile reactivate cultures and multiplication rate was observed in the combination of 5.380 mg L-1 of Kinetin and 0.093 mg L-1 of NAA in the establishment medium.